ANALISIS KEMANDIRIAN SOSIAL DAN BUDAYA MASYARAKAT BADUY SEBAGAI REPRESENTASI PEMBANGUNAN BERKELANJUTAN DALAM KERANGKA SDGS: LITERATURE REVIEW - Gadis Eka Fitri Sibarani; Aisha Fadia Salsabilla; Aprima Fitria Candra; Alvin Adam Purnomo; Shahibah Yuliani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Indonesia is characterized by social and cultural diversity in its society as a whole. As part of their cultural identity, communities still hold onto collective values, local wisdom and a close bond with the environment. One of the indigenous communities that still maintain these characteristics is the Baduy people. Baduy community has consumption pattern, local wisdom and customary system from agricultural sector up to social life that reflect the principles of sustainable development. The purpose of this study is to analyze and identify the relationship of environmental conservation, consumption pattern and the customary systems of the Baduy community in supporting sustainable development. This research is qualitative research with literature review method, by using scientific articles and books related to sociocultural aspects of the Baduy community. The results show that the consumption patterns, local wisdom and customary systems of the Baduy community are interconnected so that they support the Sustainable Development Goals (SDGs).